Sleep disorders in Parkinson’s disease - Israt Jahan (Dove Medical Press, 2009)
Israt Jahan1, Robert A Hauser2, Kelly L Sullivan1, Amber Miller1, Theresa A Zesiewicz11Department of Neurology, Parkinson’s Research Foundation, 2Departments of Neurology, Molecular Pharmacology, and Physiology, University of South Florida, Parkinson’s Disease and Movement Disorders Center, Tampa, FL, USAAbstract: Sleep disorders occur commonly in Parkinson’s disease (PD), and reduce quality of life. Sleep-related problems in PD include insomnia, restless legs syndrome, rapid eye movement sleep behavior disorder, sleep apnea, parasomnias, excessive daytime sleepiness, and sleep attacks. This article reviews sleep disorders and their treatment in PD. Keywords: insomnia, restless legs syndrome, sleep apnea